IDENTIFIKASI POTENSI DAN PROBLEMATIKAN TAPAK STADION BATAKAN BALIKPAPAN - Reny Rachmawati; Ardiyansah; Avica Widya Anggreany; Andi Muhammad Haswar (Display Architecture Journal, 2022)
The Batakan Balikpapan Stadium is a landmark and important sports building located in East Balikpapan, the site location is in the eastern industrial area of Balikpapan city which is also a tourism and city development area. This study aims to identify the potential and problems in the condition of the Batakan Balikpapan Stadium site in terms of circulation, visuals, topography, climate zoning and regulation. The research uses a qualitative descriptive research paradigm to describe the strengths and weaknesses of the site. This study found that the condition of the Batakan Balikpapan Stadium site has great potential as a sports, recreation area and as a green open space by maximizing strengths in topography, circulation and regulatory aspects, then fixing weaknesses in visual and zoning aspects.